Strategic Movement to Increase Borobudur Tourism Potentials by Female Tour Guides during the COVID-19 Pandemic - Hapsari, Prima Dona; Pramono, Bambang (Humaniora: Journal of Indonesia Culture and Society, 2023)
The research aimed to discuss the strategic movement to increase tourism potential by female tour guides for maintaining the sustainability of cultural art tourism programs due to the decreasing number of tourists visiting the objects in Borobudur during the COVID-19 pandemic; to determine the roles of female tour guides for the sustainability of cultural art tourism in Borobudur; to know how female tour guides apply English communicative skills and self-competence in their work. During the COVID-19 pandemic, tourism potential experienced a decline and sluggishness, which inevitably hit the dynamic circle of tourism, arts, culture, and the community's economy, particularly for the tourism actors in Borobudur. Before being affected by COVID-19, Borobudur's tourism and cultural potential were very dynamic and in line with the supportive programs of several Ministries of the Republic of Indonesia. The research combined both qualitative and quantitative research. It used a descriptive method by distributing a questionnaire, doing a survey, using observation, and doing an in-depth interview to collect data. Fifteen female tour guides represented their villages in Borobudur. They played a role in cultural tourism in Borobudur. The research results are, namely (1) Borobudur female tour guides develop their self-competence and enhance their English communication to support Borobudur cultural art tourism during the COVID-19 pandemic, (2) Borobudur female tour guides perform essential roles in the tourism industry and family circle by providing alternative side works, such as managing UMKM (community enterprises), running home-industry, etc., and (3) the female tour guides have English communicative competence practiced in groups by developing practical skills and communicative ethics among them.